Large-Scale Planning Address Interior Space Production Three Case Studies from Northern Minnesota - Hoganson,Howard (2004)
Applications of a forest management scheduling model to the forest situation in northern Minnesota added insight on how to better integrate management for ecological and economic conditions. Emphasis was on developing harvest schedules that recognise the value of older forest interior space (core area). Although ownership patterns in northern Minnesota are quite intermixed, results show that most of the gain from improving management schedules to produce old forest interior space can likely be achieved by the larger public landowners through careful spatial planning on their own lands. Simple management rules like cut in larger blocks are not likely to perform well because of lost opportunities to produce more interior space in the shorter term.